Effect of tetrandrine on morphine dependence in isolated guinea pig ileum. - Liu Zhong-hua; Li Jin-lian; Li Na; Tian Chun-lin; Zhang Kai-gao (Acta Pharmacologica Sinica, 2016)
AIM: To evaluate the effects of tetrandrine (Tet) and nimodipine (Nim) on the morphine (Mor) withdrawal response in the isolated guinea pig ileum. METHODS: The withdrawal contracture was elicited by addition of naloxone (Nal) (1 mumol.L-1) to the isolated naive ileum incubated with Mor (3 mumol.L-1) at 37.5 degrees C for 4 h or to the ileum obtained from Mor-dependent guinea pig. RESULTS: When Nim (0.01, 0.05, and 0.1 mumol.L-1) or Tet (1, 10, and 50 mumol.L-1) was added 1 min before Nal in the naive ilea bathed in Krebs solution containing Mor, or when the ilea from Mor-dependent guinea pigs were incubated with Nim (0.01, 0.05, and 0.1 mumol.L-1) or Tet (1, 10, and 50 mumol.L-1) for 15 min, or when Nim (5 and 10 mg.kg-1, i.p.) or Tet (15 and 30 mg.kg-1, i.p.) was administered in vivo to Mor-dependent guinea pigs, the Nal-precipitated withdrawal contracture was significantly decreased in a dose-dependent manner. CONCLUSION: Tet and Nim, Ca2+ channel blockers, could inhibit the Nal-precipitated Mor withdrawal response in the isolated guinea pig ileum.